How to Mourn for Animals? From Misanthropic Melancholia to Animal Ethical Mourning - Aaltola, Elisa; Pihkala, Panu (John Muir Institute for Environmental Studies, 2026)
The paper explores “animal ethical mourning” through three directions: 1) mourning for nonhuman animals, 2) mourning for lost human ideals, and 3) mourning with nonhuman animals. First, it investigates the political and moral significance of animal ethical mourning arguing it is a radical normative act. Second, it claims such mourning extends also to given human ideals, which our treatment of animals reveals to be forsaken. Here, it introduces “misanthropic melancholia” and argues it to form one affectively challenging yet normatively illuminating aspect of animal ethical mourning. Finally, it considers what it means to mourn with other animals. The paper’s central claim is more rituals and rhetoric are needed to evoke these aspects of animal ethical mourning.